Sublingual immunotherapy in children with allergic rhinoconjunctivitis mono-sensitized to house-dust-mites: A double-blind-placebo-controlled randomised trial - AKKOÇ, TUNÇ (W B SAUNDERS CO LTD, 2013)
Background: Although sublingual immunotherapy (SLIT) has been demonstrated to be a safe and efficient treatment in children with seasonal allergic rhinitis (AR), there is little evidence on the efficacy of SLIT with house-dust-mite (HDM) extract in children with isolated perennial AR. Objectives: We sought to assess the clinical efficacy and safety of HDM-SLIT in children with isolated allergic rhinitis-conjunctivitis mono-sensitized to HDM without asthma symptoms. Methods: Twenty-two children (aged 5-10 years) with perennial AR and conjunctivitis symptoms mono-sensitized to Dermatophagoides pteronyssinus and Dermatophagoides farinae were enrolled. During a 2 months run-in period, symptom and medication scores, lung functions, bronchial hyperreactivity, nasal provocation and skin prick tests were evaluated. Subjects were randomized to active or placebo using a double-blind method. A total of eighteen subjects were randomised to receive either active SLIT or placebo for 12 months. Daily symptom and medication scores, baseline lung functions, bronchial hyperreactivity, nasal provocation and skin prick tests were recorded and re-evaluated at the end of treatment. Results: After one year of treatment, no significant differences were detected in the between groups and within group comparisons based on total rhinitis symptom/medication scores (p > 0.05). Skin reactivity to Dermatophagoides pteronyssinus was significantly reduced in HDM-SLIT compared to placebo group (p = 0.018). A significant reduction in nasal sensitivity was observed in SLIT group after one year treatment when compared to baseline (p = 0.04). Total conjunctivitis symptoms were reduced significantly in both active and lacebo group at the end of treatment compared to baseline. The proportion of patients with nonspecific bronchial hyperreactivity increased to almost 3-fold in placebo group compared to baseline. Conclusion: HDM-SLIT was not superior to placebo in reducing isolated rhinoconjunctivitis symptoms within 12 months of treatment. However, HDM-SLIT has a modulating effect on allergen-specific nasal and skin reactivity in isolated perennial AR children. Clinical Trial Registration: The trial was registered at Anzctr.org.au number, ACTRN1261 3000315718. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allergy; Asthma; Conjunctivitis; Dust mite; Rhinitis; Sublingual immunotherapy; RHINITIS; ASTHMA; EFFICACY; CHILDHOOD; CONJUNCTIVITIS; PARAMETERS; EXTRACT; IMPACT